Can the SiMaYang Learning Model Improve Elementary School Students' Critical Thinking Skills? - Viviani Nurmala; Fery Muhamad Firdaus; Sunyono (Universitas Pendidikan Ganesha, 2023)
Low critical thinking skills are characterized by the inability of students to analyze ideas or suggestions in a more specific direction. This research aims to analyze students' critical thinking abilities by applying the Si-5 Kite (SiMaYang) learning model. This research uses a quantitative approach with a Quasi-Experimental Design type Nonequivalent Control Group Design. The population in this study was the fifth grade of elementary school with relatively low critical thinking skills based on the pretest results. The sampling technique used was purposive sampling. The number of samples in the experimental class was 30, and the number in the control class was 29. The data collection technique used is a test consisting of a pretest and a posttest. The data analysis techniques used in this research are descriptive and inferential statistical. The research results showed a significant difference in students' critical thinking abilities between the group that applied the SiMaYang learning model and the group that applied conventional methods. This can be seen based on the results of the pretest and posttest of the experimental class, which show a significant difference in students' critical thinking abilities before and after being given treatment in the form of implementing the SiMaYang learning model. So, the SiMaYang learning model can be used as an alternative learning model that can be applied to improve elementary school students' critical thinking skills.